Utilising Bint Ash-Shāţi’s Thought as a Panacea for the Misconceptions about Women Leadership in Modern Muslim Societies - OMOTOSHO Haleemah Olajumoke; SURAJU Saheed Badmus (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The spread of literacy, western civilization as well as the expansion of women’s job opportunities to men's field of endeavourhas levelled up the power tussle between men and women geometrically. Thus, women have proven to be resourceful, creative and active in ownership and shouldering responsibility as well as clamouring for participation in almost every aspect of life, especially leadership. However, several misconceptions about women leadership in Islām have risen among contemporary Muslim societies which have become impediments for some Muslim women to hold leadership positions. Base on this, this paper explored the relevance of bint al-Shati’s thought to clarifying the misconceptions surrounding women leadership in Islam. The research methods adopted were the historical method which was used in accounting for the biography of Bint Al-Shāṭi, the analytical; which aided in analysing the misconceptions about women's leadership in Islam, coupled with the views of Bint Al-Shāṭi and Muslim scholars and the phenomenological method which was used to relate the discussion to contemporary society. The research findings revealed that Bint Shāṭi challenged interpretations of religious texts that have been used to justify the marginalization and exclusion of women from leadership affairs. She further provided a progressive interpretation that promotes gender justice and equity and encouraged women to actively participate in public decision-making without exceeding their limitations. The paper concluded that her thoughts provided valuable insights into natural dispositions surrounding women's leadership in Islam and emphasized the women potential to be effective leaders by advocating education, equitable opportunities, and reinterpreting religious texts within an Islamic framework. The paper recommended that more attention and awareness should be paid to the sensitivity of women's issues in Islām to resolve the differences experienced in modern Muslim societies.